TINJAUAN YURIDIS URGENSI PEMBERANTASAN KORUPSI DI INDONESIA - Agustia Ayu Budhiyani; Ardi Alvianto Prihandoyo (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2014)
AbstractThe purpose of the article is to explain about corruption in Indonesia which it grows and systemically carried by certain groups. The existence of goverment regulations about the eradication of corruption doesn’t make sure if it’s effective for eradicating corruption. The poor of law enforcement and also many inhibiting factors make corruption are difficult to anticipate. Moreover the article also explain about prevention of corrupting act in the form of strategies and improvement efforts in combating corruption in Indonesia. As conclusion should made an integrity of enforcing the law start from revision, revitalization of forceful regulations and harmonization of law enforcer also governance institution itself in order to decrease the possibilities for corruption act with the result to didn’t make any financial loss for the state and didn’t harm another people.Keywords: corruption, anti-corruption regulationsAbstrakArtikel ini bertujuan untuk mengkaji secara mendalam mengenai tindak pidana korupsi di Indonesia yang berkembang dan dilakukan secara sistemik oleh golongan tertentu. Adanya peraturan yang mengatur tentang pemberantasan korupsi belum tentu efektif untuk memberantas tindak pidana korupsi. Lemahnya kebijakan penegakan hukum dan juga banyaknya faktor penghambat membuat tindak pidana korupsi sulit diantisipasi. Selain itu dikaji juga tindakan pencegahan korupsi yaitu berupa strategi maupun upaya perbaikan dalam memberantas korupsi di Indonesia. Kesimpulannya harus dilakukan integritas dalam menegakan hukum dimulai dari revisi, revitalisasi peraturan yang tegas dan harmonisasi aparat penegak hukum maupun pemerintah sendiri agar mempersempit kemungkinan terjadinya korupsi sehingga tidak merugikan negara maupun masyarakat. Katakunci: korupsi, peraturan anti-korupsi